New distributional records for Gyrinidae (Insecta: Coleoptera) on New Guinea and nearby islands, with a checklist of the New Guinea species - Polhemus, Dan A. (Zootaxa, 2011)
New distribution records are provided for the following 16 taxa of Gyrinidae on New Guinea, some of which have not been documented since their original type series were collected in the late 1800s or early 1900s: Porrorhynchus (Rhomborhynchus) depressus depressus Régimbart; Porrorhynchus (Rhomborhynchus) depressus misoolensis Ochs new combination; Dineutus (Rhombodineutus) pectoralis pectoralis Régimbart; Dineutus (Rhombodineutus) pectoralis biakensis Brinck; Dineutus (Rhombodineutus) pectoralis monticola Ochs; Dineutus (Rhombodineutus) heurni Zimmerman; Dineutus (Rhombodineutus) silenus Brinck; Dineutus (Rhombodineutus) sinuaticollis Zimmerman; Dineutus (Rhombodineutus) virescens Ochs; Dineutus (Rhombodineutus) chalybeus Zimmerman; Dineutus (Rhombodineutus) helleri stueberi Ochs; Dineutus (Rhombodineutus) tetracanthus tetracanthus Régimbart; Dineutus (Merodineutus) archboldianus Ochs; Dineutus (Merodineutus) loriae Régimbart; Dineutus (Merodineutus) macrochirus Régimbart; and Dineutus (Spinosodineutes) neohollandicus Ochs. New distribution records are also provided for Dineutus (Dineutus) regimbarti regimbarti Régimbart from East Timor. The type-locality of Dineutus (Rhombodineutus) chalybeus is constrained to Yule Island, on the Gulf of Papua. Updated distribution maps are provided for all the New Guinea species above, a table is included summarizing currently documented ranges of elevation and water temperature for all species treated, and a checklist of all species of Gyrinidae currently known from New Guinea and nearby islands is provided, with species assigned to putative areas of freshwater endemism within the island.